2012
DOI: 10.4028/www.scientific.net/amr.488-489.72
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy Observation on Nanocellulose from Kenaf Fibre

Abstract: Conventional fibre size has large surface area for binding site while nanocellulose posses higher surface area thus making more available binding site for fibre-matrix interaction. Kenaf has poor surface properties before treated. Treatment was applied to overcome this problem with alkali followed by acidic treatment. The nanocellulose has been produced from kenaf core (hibiscus cannabinus) by chemi-mechanical method. The fibre was treated with alkali followed by acidic treatment (HCl). Treated fibres were mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The peaks in the 3,344-3,415 and 1,635-1,645 cm -1 regions were attributed to O-H stretching and bending vibrations, respectively, of hydrogen bonded hydroxyl (OH) groups of absorbed water, aliphatic primary and secondary alcohols found in cellulose, hemicellulose, and carboxylic acids in extractives. 12,21 The peaks at 1,701-1,737 cm -1 in raw OPF corresponded to the C=O stretching of hemicellulose and lignin while in CNC, the peaks were shorter which indicated lesser amount of the chemical components available in the sample. It can also be observed that the peaks at 1,509-1,609 cm -1 which corresponded to C=C aromatic skeletal vibration of lignin only appeared in raw OPF.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…The peaks in the 3,344-3,415 and 1,635-1,645 cm -1 regions were attributed to O-H stretching and bending vibrations, respectively, of hydrogen bonded hydroxyl (OH) groups of absorbed water, aliphatic primary and secondary alcohols found in cellulose, hemicellulose, and carboxylic acids in extractives. 12,21 The peaks at 1,701-1,737 cm -1 in raw OPF corresponded to the C=O stretching of hemicellulose and lignin while in CNC, the peaks were shorter which indicated lesser amount of the chemical components available in the sample. It can also be observed that the peaks at 1,509-1,609 cm -1 which corresponded to C=C aromatic skeletal vibration of lignin only appeared in raw OPF.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Sihag et al [381] prepared NCs from sawdust by cryo-crushing and ultrasonication having NCs has a size of 10-100 μm. Surip et al [382] produced NCs by pulverisette and cryocrushing.…”
Section: Mechanical Treatment For Nanocellulose Productionmentioning
confidence: 99%
“…Various mechanical shearing methods or a combination of both chemical and mechanical methods can be used to obtain NFC. For example, Surip et al [ 33 ] had produced NFC of 40–200 nm in diameter from kenaf fiber which was treated with alkali followed by acidic treatment (HCl) before it was mechanically processed by using pulverisette and cryo-crushing. In general NFC is a material composed by nanosized cellulose fibrils with a high aspect ratio (length to width ratio).…”
Section: Isolation and Chemical Modifications Of Cellulosementioning
confidence: 99%